Hyaluronic acid hydrogel based on cross-linking modification of copper ions as well as preparation method and application of hyaluronic acid hydrogel

Modified hyaluronic acid hydrogel through copper ion crosslinking, the problems of complex preparation and insufficient antibacterial properties of existing HA are solved, and the antibacterial and anti-inflammatory and degradation resistance of the materials are realized. It is suitable for subcutaneous filling, showing the medical beauty field potential.

CN119286070AActive Publication Date: 2025-01-10SHAANXI UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411532501.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-10
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing modified hyaluronic acid (HA) has problems such as complex preparation process, potential risk of chemical contamination, lack of antibacterial properties and fast degradation rates in clinical applications, which affect its safety and use effect.

Method used

Using hyaluronic acid hydrogel based on copper ion crosslinking modification, the combination of Cu2+ with hyaluronic acid and crosslinking agent is used to form a material with antibacterial, anti-inflammatory and degradation resistance, and the material is improved by using the continuous release and crosslinking reaction of Cu2+. mechanical strength and stability.

Benefits of technology

It realizes the antibacterial and anti-inflammatory effect of the material, extends the filling maintenance time, improves biocompatibility and mechanical properties, and reduces the risk of chemical pollution. It is suitable for subcutaneous filling and medical beauty fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286070A_ABST
    Figure CN119286070A_ABST
Patent Text Reader

Abstract

The invention discloses hyaluronic acid hydrogel based on cross-linking modification of copper ions as well as a preparation method and application of the hyaluronic acid hydrogel, and belongs to the technical field of biomedical materials. Dissolving Cu < 2 + > in sterile deionized water to obtain a Cu < 2 + > solution; adding hyaluronic acid into the Cu < 2 + > solution, and uniformly mixing to obtain Cu < 2 + > liquid hydrogel; and adding a cross-linking agent into the Cu < 2 + > liquid hydrogel, uniformly mixing, carrying out light-shielding cross-linking, and cleaning to obtain the hyaluronic acid hydrogel based on copper ion cross-linking modification. The preparation conditions are mild, the method is simple, reagents are few, no violent reaction exists, the cost is low, industrialization is easy to achieve, and the prepared hyaluronic acid hydrogel is excellent in degradation resistance, excellent in mechanical performance, good in biocompatibility, long in in-vivo lasting time and suitable for subcutaneous filling and other scenes in the field of biomedical materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and specifically relates to a hyaluronic acid hydrogel based on copper ion cross-linking modification, and a preparation method and application thereof. Background Art

[0002] With the improvement of people's quality of life and the rapid development of medical beauty technology, the public is paying more and more attention to the improvement of facial depression and the delay of aging. These demands are often accompanied by the normal structural defects of soft tissues such as subcutaneous fat, collagen and muscle. In order to repair the defects, many artificial fillers have been widely used in clinical soft tissue filling. Among them, hyaluronic acid (HA) is a natural, non-immunogenic glycosaminoglycan composed of D-glucuronic acid and N-acetyl-D-aminoglucose disaccharide units connected by glycosidic bonds. Due to its high water retention capacity and unique viscoelasticity, HA is highly favored in the medical beauty industry and is increasingly used as a skin filler to enhance skin contours, smooth fine lines and wrinkles, and achieve a younger and firmer skin condition.

[0003] Although HA is widely used due to its excellent biocompatibility, the risk of microbial contamination of HA cannot be ignored during clinical injection operations. Any tiny bacterial or viral contamination may lead to serious postoperative infection and inflammatory response, which poses a potential threat to the patient's health. In addition, the rapid biodegradation rate of these filling materials leads to a limited duration of their effects. Patients are usually required to undergo frequent repeated injections to maintain the cosmetic effect, which not only increases the economic burden on patients, but also increases the complexity and discomfort of treatment, making the clinical application of HA face challenges and limitations. Therefore, modified HA came into being.

[0004] The current methods for modifying HA include the 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride method, the methacrylation method, and the glutaraldehyde method. However, these methods have the following problems in clinical application: 1) The preparation process involves complex chemical synthesis and purification steps, which not only increases the manufacturing cost of the product, but also may introduce potential chemical contamination risks, affecting the safety and stability of the product; 2) Lack of antibacterial properties; 3) Fast degradation rate. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a hyaluronic acid hydrogel based on copper ion cross-linking modification and its preparation method and application, so as to solve the problems of complex preparation process, lack of antibacterial property and fast degradation rate of existing modified HA.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The first aspect of the present invention discloses a hyaluronic acid hydrogel based on copper ion cross-linking modification, comprising Cu 2+ , hyaluronic acid and a cross-linking agent, the Cu 2+ The concentration is 1~2 mM.

[0007] Preferably, Cu 2+ Derived from copper sulfate, copper gluconate, copper citrate, copper carbonate or copper lactate.

[0008] Preferably, the concentration of hyaluronic acid is 1 wt%~2 wt%.

[0009] Preferably, the cross-linking agent comprises 1-ethyl-(3-dimethylaminopropyl)carbodiimide at a concentration of 2 wt% to 3 wt% and N-hydroxysuccinimide at a concentration of 0.667 wt% to 2 wt%.

[0010] The second aspect of the present invention discloses a method for preparing the above-mentioned hyaluronic acid hydrogel based on copper ion cross-linking modification, comprising the following steps: 2+ Dissolve in sterile deionized water to obtain Cu 2+ Solution; in Cu 2+ Add hyaluronic acid to the solution and mix well to obtain Cu 2+ Liquid hydrogel; in Cu 2+ A cross-linking agent is added to the liquid hydrogel and mixed, and then cross-linked in the dark and washed to obtain a hyaluronic acid hydrogel modified by copper ion cross-linking.

[0011] Preferably, the mixing is achieved by stirring at 40-50°C at a speed of 300-600 rpm.

[0012] Preferably, crosslinking is carried out in the dark for at least 12 h.

[0013] Preferably, sterile deionized water is used for washing, and the amount of sterile deionized water added is 4 to 6 times the volume of the light-shielded cross-linked product.

[0014] Preferably, clean 8 to 12 times.

[0015] The third aspect of the present invention discloses the use of the above copper ion cross-linked modified hyaluronic acid hydrogel in subcutaneous filling.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a hyaluronic acid hydrogel modified by copper ion cross-linking. Based on the metal ion-carbodiimide cross-linking strategy, copper ions are loaded into the modified hyaluronic acid gel to form a hyaluronic acid hydrogel modified by copper ion cross-linking. 2+ The sustained release of Cu can be antibacterial and anti-inflammatory, making it impossible for bacteria to infect the injured area;2+ The sustained release of can degrade hyaluronidase in the body and enhance the degradation resistance of hyaluronic acid hydrogel under the skin, thereby achieving better antibacterial and anti-inflammatory effects and longer filling maintenance time. On the other hand, the low-concentration HA solution is converted into a solid by a cross-linking agent to promote the cross-linking between hyaluronic acid molecules, which can not only improve the mechanical strength and stability of hyaluronic acid, but also effectively prevent the degradation of hyaluronidase. At the same time, experiments have shown that the hyaluronic acid hydrogel has strong antibacterial properties, good biocompatibility, and excellent mechanical properties. It will continuously release copper ions (Cu) before the wound heals. 2+ ), shows great potential in the field of medical beauty, so the hyaluronic acid hydrogel can be used in scenarios such as subcutaneous filling in the field of biomedical materials.

[0017] Further, EDC is a water-soluble carbodiimide, which reacts with the carboxyl group in hyaluronic acid to form an activated amide intermediate. Subsequently, NHS reacts with the activated intermediate to generate a more stable NHS ester, thereby promoting the cross-linking between hyaluronic acid molecules. This process not only improves the mechanical strength and stability of hyaluronic acid, but also effectively prevents the degradation of hyaluronidase. The by-product of this cross-linking reaction is urea with good solubility in water, which is easily removed in the cleaning step.

[0018] The present invention provides a method for preparing a hyaluronic acid hydrogel based on copper ion cross-linking modification, wherein hyaluronic acid is dissolved in Cu 2+ In a sterile deionized water solution, magnetic stirring is performed until dissolved, and then an appropriate amount of cross-linking agent is added and magnetic stirring is performed to dissolve, and urea is removed by multiple washings, and finally a hyaluronic acid hydrogel based on copper ion cross-linking modification is obtained. The preparation process is simple, the reaction conditions are mild, the reagents are few and there is no violent reaction, the cost is low, it is easy to industrialize, and it is suitable for popularization and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 : is a morphological diagram of the gelation of hyaluronic acid hydrogel based on copper ion cross-linking modification; wherein A is the prepared hyaluronic acid hydrogel based on copper ion cross-linking modification, B is the hyaluronic acid hydrogel before pressing, C is the hyaluronic acid hydrogel during pressing, and D is the hyaluronic acid hydrogel after pressing; Figure 2 The figure is a result diagram of the injectability of hyaluronic acid hydrogel modified by copper ion crosslinking; A is a result diagram of the viscosity of hyaluronic acid hydrogel modified by copper ion crosslinking as a function of shear rate, and B is a schematic diagram of the injection of hyaluronic acid hydrogel modified by copper ion crosslinking through a 10 mL syringe (No. 7 needle); Figure 3 Based on the copper ion cross-linking modified hyaluronic acid hydrogel for Cu 2+ Results graph of release rate; Figure 4 The results of plate coating show that hyaluronic acid hydrogel modified by copper ion cross-linking kills Staphylococcus aureus (A) and Escherichia coli (B); Figure 5 The diagram shows the cytotoxicity of hyaluronic acid hydrogel modified by copper ion cross-linking to human skin fibroblasts (A) and human umbilical vein endothelial cells (B); Figure 6 The figure is a schematic diagram of the subcutaneous injection test of hyaluronic acid hydrogel modified by copper ion crosslinking in Wistar rats; wherein A is the appearance and anatomical diagram of the rat's back, B is the HE and Masson staining results of the skin tissue of the rat's back in contact with the hyaluronic acid hydrogel modified by copper ion crosslinking, and C is the weight retention rate result diagram of the hyaluronic acid hydrogel modified by copper ion crosslinking in the rat's subcutaneous tissue. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0021] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0022] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0023] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0024] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0025] The present invention provides a hyaluronic acid hydrogel based on copper ion cross-linking modification, which comprises, by weight: 96.153 parts of sterile deionized water, 0.00015 parts of Cu 2+ , 0.01098 parts of HA, 0.02005 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 0.00602 parts of N-hydroxysuccinimide (NHS).

[0026] The present invention provides a method for preparing the above-mentioned subcutaneous filling gel material, comprising the following steps: 1. Cu 2+ Dissolve in sterile deionized water and stir at room temperature to obtain a light blue Cu solution with a concentration of 1~2 mM. 2+ Solution; Among them, the Cu 2+ Sources include, but are not limited to, copper sulfate (CuSO4), copper gluconate, copper citrate, copper carbonate, and copper lactate.

[0027] 2. Add HA powder to light blue Cu 2+ The solution was stirred magnetically at 300-600 rpm in a 40-50°C water bath to obtain a light blue Cu 2+ Liquid hydrogel; Among them, the light blue Cu 2+ In the liquid hydrogel, the concentration of HA is 1wt%~2 wt%.

[0028] 3. In the light blue Cu 2+ Add 2wt%~3wt% EDC to the liquid hydrogel and let it react for 15~20min. Then add 0.667wt%~2wt% NHS and stir magnetically at 300~600 rpm in a 40~50℃ water bath to obtain a dark blue Cu 2+ Liquid hydrogel; 4. Dark blue Cu 2+ The liquid hydrogel was crosslinked in the dark for at least 12 h, and then washed with sterile deionized water 8 to 12 times for two days to obtain a hyaluronic acid hydrogel modified by copper ion crosslinking; Among them, the amount of sterile deionized water added for each cleaning is Cu 2+ 4~6 times the volume of solid hydrogel.

[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0030] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0031] 1. Preparation of hyaluronic acid hydrogel based on copper ion cross-linking modification 1. Accurately weigh 0.00015 parts by weight of CuSO4 powder and dissolve it in 96.153 parts by weight of deionized water. Stir evenly at 25°C to form a light blue CuSO4 solution with a final concentration of 1 mM. 2. The light blue CuSO4 solution obtained in step 1 was transferred to a water bath magnetic stirrer at 45°C and 400 rpm, 0.01098 parts of HA powder was added, and magnetic stirring was performed for 3 h to form a uniform light blue CuSO4 liquid hydrogel; Among them, the concentration of HA in the light blue CuSO4 liquid hydrogel is 1 wt%; 3. Add 0.02005 parts of EDC powder to the light blue CuSO4 liquid hydrogel, dissolve evenly and react for 15 minutes, then add 0.667 parts of NHS powder, and continue cross-linking for 15 minutes at a speed of 300-600 rpm in a 40-50°C water bath to obtain a dark blue CuSO4 liquid hydrogel; Among them, in the dark blue CuSO4 liquid hydrogel, the concentration of EDC is 2 wt% and the concentration of NHS is 0.67 wt%; 4. The dark blue CuSO4 liquid hydrogel was transferred to a sealed container, anaerobic crosslinked for 12 h in the dark, and washed with sterile deionized water 8 times to obtain a hyaluronic acid hydrogel modified by copper ion crosslinking, such as Figure 1 As shown in A.

[0032] 2. Performance Test 1. Recovery ability test A certain pressure was applied to the prepared hyaluronic acid hydrogel based on copper ion cross-linking modification, and the morphology of the hyaluronic acid hydrogel was observed after the pressure was removed.

[0033] The results are as follows Figure 1 As shown in B~C, the hyaluronic acid hydrogel modified by copper ion cross-linking maintains its own integrity due to its high-strength internal network, and will quickly return to its original state after being pressed.

[0034] 2. Injectability test 1) The injectability of the prepared hyaluronic acid hydrogel based on copper ion cross-linking modification was characterized by rheometer. In the viscosity test, the viscosity of the hyaluronic acid hydrogel and the hyaluronic acid hydrogel after 30 days were measured as a function of shear rate (1-100 1 / s).

[0035] The results are as follows Figure 2 As shown in Figure A, as the shear rate increases, the viscosity decreases rapidly, and the hyaluronic acid hydrogel modified by copper ion cross-linking exhibits shear thinning phenomenon, which theoretically verifies the injectability of hyaluronic acid hydrogel. Moreover, the hyaluronic acid hydrogel still has similar properties to freshly prepared gel after being placed for 30 days.

[0036] 2) The prepared copper ion cross-linked modified hyaluronic acid hydrogel was loaded into a 10 mL syringe (No. 7 needle), and the hyaluronic acid hydrogel was spelled by pressing the syringe to test the injectability of the hyaluronic acid hydrogel.

[0037] The results are as follows Figure 2 As shown in B, the hyaluronic acid hydrogel modified by copper ion cross-linking can be smoothly extruded through a 10 mL syringe (7-gauge needle), and the words Injection, A, B, and C can be fluently written using the syringe, further verifying the Cu 2+ Injectability of hydrogels.

[0038] 3. Cu 2+ Release ability test Inductively Coupled Plasma Mass Spectrometry (ICP-MS) was used to investigate the Cu ions in the hyaluronic acid hydrogels modified by copper ions cross-linking in saline. 2+ Release rate determination. The specific steps are as follows: accurately weigh 5 g of hyaluronic acid hydrogel based on copper ion cross-linking modification into a 50 mL centrifuge tube, add 45 mL of sterile saline, and continue to soak the gel in a shaker at 37°C and 400 rpm. Take 1 mL of hyaluronic acid hydrogel extract at 0, 3, 6, 12, 24, 48, 72, and 96 h, respectively, and measure the Cu in the liquid. 2+ Content, and then calculate Cu 2+ Release rate.

[0039] The results are as follows Figure 3 As shown in Figure 2, the copper ion cross-linked modified hyaluronic acid hydrogel slowly released Cu in saline within 72 h. 2+ , the released Cu 2+It not only has antibacterial and anti-inflammatory effects, but also can inactivate hyaluronidase in the body. 2+ The release amount is similar, further illustrating that most of the Cu 2+ It participates in the complexation reaction with the gel rather than being completely released.

[0040] 4. Antibacterial ability test Accurately weigh 0.3 g of hyaluronic acid hydrogel based on copper ion cross-linking modification and hyaluronic acid hydrogel based on copper ion cross-linking modification after 30 days of storage; prepare OD 600 = 0.1 Escherichia coli ( Escherichia coli ) and Staphylococcus aureus ( Staphylococcus aureus ) bacterial solution. In a 50 mL centrifuge tube, the copper ion cross-linked modified hyaluronic acid hydrogel was co-incubated with 200 μL bacterial solution at 37°C and 400 rpm for 9 h. At the same time, in another 50 mL centrifuge tube, the copper ion cross-linked modified hyaluronic acid hydrogel after 30 days was co-incubated with 200 μL bacterial solution at 37°C and 400 rpm for 9 h. The total number of bacterial colonies in each group was determined by the plate coating experiment to further clarify the effect of Cu on the growth of hyaluronic acid hydrogel. 2+ Antibacterial ability of hydrogels.

[0041] The results are as follows Figure 4 As shown in the figure, the hyaluronic acid hydrogel modified by copper ion cross-linking killed almost all Staphylococcus aureus and Escherichia coli, and the bactericidal effect of the hyaluronic acid hydrogel remained unchanged after being placed for 30 days, which proved that the hyaluronic acid hydrogel modified by copper ion cross-linking had long-lasting good antibacterial properties.

[0042] 5. In vitro biosafety test The CCK-8 method was used to evaluate the in vitro cytotoxicity of hyaluronic acid hydrogels modified by copper ion cross-linking. 3000 human skin fibroblasts (HSF cells) and 3000 human umbilical vein endothelial cells (HUVEC cells) were seeded in 96-well plates and cultured for 24 h. 5 g of hyaluronic acid hydrogels modified by copper ion cross-linking were immersed in 45 mL DMEM-F12 medium (containing 5% fetal bovine serum and 1% double antibody) at 4 ° C for 24 h, and then the leaching solution was used to replace the medium for continued culture for 1, 3, and 5 days. After CCK-8 treatment for 2 h, the cell viability was measured by microplate reader at 450 nm.

[0043] The results are as follows Figure 5 As shown, the viability of both cells exceeded 90% within 5 days under the culture conditions of hyaluronic acid hydrogel extract modified by copper ion cross-linking. These results indicate that hyaluronic acid hydrogel modified by copper ion cross-linking has good in vitro biocompatibility.

[0044] 6. Subcutaneous filling experiment in rats The Cu ion cross-linking modified hyaluronic acid hydrogel was injected subcutaneously on the back of Wistar rats to evaluate the 2+ In vivo degradation and biocompatibility of hydrogels. During the modeling process, the backs of Wistar rats were depilated, and 2 mL of hyaluronic acid hydrogel based on copper ion cross-linking modification was subcutaneously injected into the backs of rats using a 10 mL syringe (No. 7 needle). The rats were euthanized on the 7th, 15th, and 30th days after injection, and the skin tissue in the hyaluronic acid hydrogel injection area was cut open, and the appearance and weight of the hydrogel were recorded. The skin in contact with the hyaluronic acid hydrogel was taken for HE staining and Masson staining.

[0045] Skin tissue appearance and weight results Figure 6 As shown in A and C, the hyaluronic acid hydrogel modified by copper ion cross-linking was successfully injected subcutaneously into rats. Due to its good mechanical properties, it supported the skin for a long time and thus had a good subcutaneous filling effect. Moreover, after 30 days of observation, the mass of the hyaluronic acid hydrogel modified by copper ion cross-linking only degraded by 11.74%.

[0046] The staining results are as follows Figure 6 As shown in Figure 2B, no obvious inflammatory response and tissue necrosis were observed in the HE and Masson staining images, which further confirmed the low in vivo toxicity and biocompatibility of the hyaluronic acid hydrogel modified by copper ion cross-linking.

[0047] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A hyaluronic acid hydrogel based on copper ion cross-linking modification, characterized in that: Including Cu 2+ , hyaluronic acid and a cross-linking agent, the Cu 2+ The concentration is 1~2 mM.

2. A hyaluronic acid hydrogel based on copper ion cross-linking modification according to claim 1, characterized in that: Cu 2 + Derived from copper sulfate, copper gluconate, copper citrate, copper carbonate or copper lactate.

3. The hyaluronic acid hydrogel based on copper ion cross-linking modification according to claim 1, characterized in that: The concentration of hyaluronic acid is 1 wt%~2 wt%.

4. The hyaluronic acid hydrogel based on copper ion cross-linking modification according to claim 1, characterized in that: The cross-linking agent includes 1-ethyl-(3-dimethylaminopropyl)carbodiimide with a concentration of 2 wt% to 3 wt% and N-hydroxysuccinimide with a concentration of 0.667 wt% to 2 wt%.

5. The method for preparing the hyaluronic acid hydrogel based on copper ion cross-linking modification according to any one of claims 1 to 4, characterized in that: The following steps are included: 2+ Dissolve in sterile deionized water to obtain Cu 2+ Solution; in Cu 2+ Add hyaluronic acid to the solution and mix well to obtain Cu 2+ Liquid hydrogel; in Cu 2+ A cross-linking agent is added to the liquid hydrogel and mixed, and then cross-linked in the dark and washed to obtain a hyaluronic acid hydrogel modified by copper ion cross-linking.

6. The method for preparing the hyaluronic acid hydrogel based on copper ion cross-linking modification according to claim 5, characterized in that: Mixing was achieved by stirring at 300-600 rpm at 40-50°C.

7. The method for preparing the hyaluronic acid hydrogel based on copper ion cross-linking modification according to claim 5, characterized in that: Crosslink for at least 12 h in the dark.

8. The method for preparing the hyaluronic acid hydrogel based on copper ion cross-linking modification according to claim 5, characterized in that: The mixture was washed with sterile deionized water, and the amount of sterile deionized water added was 4 to 6 times the volume of the light-shielded cross-linked product.

9. The method for preparing the hyaluronic acid hydrogel based on copper ion cross-linking modification according to claim 5, characterized in that: Wash 8 to 12 times.

10. Use of the hyaluronic acid hydrogel modified by copper ion cross-linking according to any one of claims 1 to 4 in subcutaneous filling.

Citation Information

Patent Citations

  • Copper ion antibacterial hydrogel as well as preparation method and application thereof

    CN112480434A

  • Hyaluronic acid gel, method for producing the hyaluronic acid gel and medical product with the hyaluronic acid gel

    EP2647649A1

  • Injectable Hyaluronic Acid Derivative Hydrogel Using Click Chemistry, Preparation Method Thereof and Method For In Vivo Gelation Using The Same

    KR1020170042986A

  • Dermal injectable sterile composition

    US20150272851A1

  • Hyaluronic acid gel with a divalent zinc cation

    US20190351105A1